It takes Two to Tango? Understanding the Co‐production of Public Services by Integrating the Services Management and Public Administration Perspectives. (7th August 2013) - Osborne, Stephen P.; Strokosch, Kirsty
Abstract : We propose an important theoretical development for our understanding of the co‐production of public services. It combines the insights from both public administration and services management theory to produce a novel typology of co‐production. This clarifies its role at the operational and strategic levels, as well as its potential for transformational change in public services. Understanding co‐production in this way provides a basis through which to explore a whole range of dimensions of co‐production that were previously undifferentiated.